MINIMISASI BIAYA PRODUKSI PADA UD. AMINO MALANG - Deni Firmansyah (Manajemen Bisnis, 2011)
Jurusan Manajemen Fakultas Ekonomi UMMEmail : deni.bond@gmail.comABSTRACTThis study, entitled “Cost of Production Minimization at UD. Amino Malang”. The purpose is to determinethe exact amount of production in July, August and September 2011 which having minimize cost ofproduction. Analysis method is the Linear Programming Simplex Method approach. The method oflinear programming is a mathematical method or technique that is used to assist managers in makingdecisions regarding the determination of the amount of labor, raw materials, capital machinery andworking hours. Based on the method of Linear Programming, it can be known that the amount ofnormal production in July 2011 at 120.404 units, the number of normal production in August 2011 at118.800 units and the amount of overtime production in August 2011 at 8.325 units, the number ofnormal production of 123.987 units in September 2011 and the company bear the total production costat least Rp. 114. 840. 069, -.Keywords: total production, production cost, minimization.